Assessing the Role of Emotional Intelligence in Team Performance Case study at Al Mujtama Islamic Boarding School 4 Cianjur - Janitra, Olief Zaki; Supratikta, Hadi (Indonesian Development of Economics and Administration Journal, 2024)
Emotional intelligence (EI) has emerged as a crucial factor in understanding team dynamics and performance within service organizations. This paper presents a conceptual framework that assesses the role of emotional intelligence in enhancing team performance, specifically tailored for service-oriented contexts. The framework integrates key components of emotional intelligence, including self-awareness, self-regulation, social awareness, and relationship management, with team dynamics such as collaboration, communication, and conflict resolution. The paper begins by defining emotional intelligence and its relevance in the service industry, highlighting its impact on individual and team behaviors. It then outlines the conceptual framework, detailing how each aspect of emotional intelligence contributes to team effectiveness and performance. The framework emphasizes the importance of developing emotional intelligence skills among team members and leaders to foster a positive work environment and improve overall team outcomes. Furthermore, the paper discusses the potential challenges and barriers faced in implementing emotional intelligence practices in service organizations, such as resistance to change and the need for training and development programs. Strategies for overcoming these challenges and promoting a culture of emotional intelligence within teams are explored, drawing on examples from successful case studies and empirical research. Through a comprehensive review of existing literature and theoretical perspectives, this paper offers insights into the potential benefits of integrating emotional intelligence into team development strategies within service organizations. Practical implications and recommendations for implementing the framework are also discussed, aiming to guide organizations in enhancing team performance through a deeper understanding and application of emotional intelligence principles